2019
DOI: 10.5539/jas.v11n8p90
|View full text |Cite
|
Sign up to set email alerts
|

Ants Associated to Loranthaceae in an Agroecosystem Based on Cocoa Trees in Nkolbisson (Yaounde: Cameroon)

Abstract: The present study was carried out in order to identify the ant fauna and her potential role as auxiliary of an agricultural system based on cocoa trees leeched by Loranthaceae, in Nkolbisson neighborhood in Yaoundé (Cameroon). The work was conducted from May to September 2015. An inventory of all woody species and the associated ant fauna was carried out beforehand, followed by an inventory of the ant fauna associated couples Theobroma cacao/Loranthaceae during periods of non-flowering, flowering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, this is the first known case of occupation of this species on cocoa trees in Cameroon. The work of Mony et al (2009), Dibong et al (2011), Lodoh et al (2013, Ondoua et al (2016), andJueya et al (2019) rather reported the presence of Phragmanthera batangue, Tapinanthus preussii, Tapinanthus bangwensis as well as Phragmanthera capitata as Loranthaceae recorded respectively in the camp of the chiefdom of Ndogbong in Douala, of Sodecao in Nkoemvone and of Yaounde in Nkolbisson.…”
Section: Inventory Of Myrmecofaunamentioning
confidence: 99%
“…However, this is the first known case of occupation of this species on cocoa trees in Cameroon. The work of Mony et al (2009), Dibong et al (2011), Lodoh et al (2013, Ondoua et al (2016), andJueya et al (2019) rather reported the presence of Phragmanthera batangue, Tapinanthus preussii, Tapinanthus bangwensis as well as Phragmanthera capitata as Loranthaceae recorded respectively in the camp of the chiefdom of Ndogbong in Douala, of Sodecao in Nkoemvone and of Yaounde in Nkolbisson.…”
Section: Inventory Of Myrmecofaunamentioning
confidence: 99%